Implementasi Moora Berbasis Web pada Penentuan Kelayakan Penerima Bantuan Siswa Miskin - Aron Saputra Sirait; M. Safii; Indra Gunawan (Yayasan Pendidikan Penelitian Pengabdian ALGERO, 2021)
The Poor Student Assistance Program (BSM) is an aid from the government with the aim that poor children who excel are able to continue schooling. So that in order to minimize this assistance can be channeled properly on target, it is necessary to conduct a fairly strict selection based on the criteria that have been set. This study proposes the use of the website-based Moora method to overcome this problem. The MOORA method is very simple, stable, and powerful, even this method does not require an expert in mathematics to use it and does not require complicated mathematical calculations. The BSM assistance that will be discussed in this research is SD NEGERI 127696 Pematangsiantar City using 7 criteria, namely: Parent's Occupation, Income, Number of Dependents, Attendance, Last Semester Grades, Academic Achievement and Personality. The sample data used were 18 students. This study resulted in the highest value alternative on behalf of Ade Putri Mekaria Laila with an Optimization value of 2.22692. So it can be concluded that the Moora method can be used as a decision support method in the selection of BSM recipients.